Removal of Acid Orange 3 from Aqueous Solution by Activated Carbon Adsorption - LI*, JI-TAI; BAI, BO; SONG, YA-LI (Asian Journal of Chemistry, 2009)
Removal of acid orange 3 from aqueous solution by activated carbon adsorption was studied. The optimal adsorption conditions for the removal of acid orange 3 aqueous solution were pH = 0.5, activated carbon 500 mg L-1, initial concentrations of the dye 100 mg L-1 and T = 35 ºC, a removal efficiency of 98 % was achieved within 1 h. Kinetic data of adsorption were well fitted the pseudo-second-order kinetic model and the Langmuir isotherm. The approach may be applied to treat the industrial wastewater containing acid orange 3 if appropriate conditions are selected.